2017
DOI: 10.1371/journal.pone.0172836
|View full text |Cite
|
Sign up to set email alerts
|

Foraging niche segregation in Malaysian babblers (Family: Timaliidae)

Abstract: Tropical rainforests are considered as hotspots for bird diversity, yet little is known about the system that upholds the coexistence of species. Differences in body size that are associated with foraging strategies and spatial distribution are believed to promote the coexistence of closely related species by reducing competition. However, the fact that many babbler species do not differ significantly in their morphology has challenged this view. We studied the foraging ecology of nine sympatric babbler specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Vertical niche partitioning has been found in a range of diving (Cimino et al., ; Kokubun et al., , ; Mori & Boyd, ) and arboreal (MacArthur, ; Mansor & Ramli, ; Slagsvold, ) species where they occur in sympatry. We found that, while dive depths overlapped considerably, chinstraps dived to significantly deeper depths than Adélies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertical niche partitioning has been found in a range of diving (Cimino et al., ; Kokubun et al., , ; Mori & Boyd, ) and arboreal (MacArthur, ; Mansor & Ramli, ; Slagsvold, ) species where they occur in sympatry. We found that, while dive depths overlapped considerably, chinstraps dived to significantly deeper depths than Adélies.…”
Section: Discussionmentioning
confidence: 99%
“…Competition within and between species exerts strong influences over population dynamics, community structure and species distributions (Hardin, 1960;MacArthur, 1968). The potential for competition is particularly intense in communities where closely related species breed sympatrically at high densities and share limited food resources (MacArthur, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations were performed by only one observer to reduce bias at selected service wires in the town using a modified scan sampling method at 5-minute intervals following Altmann (1974), Martin and Bateson (1993), and Samson and Ramakrishnan (2016). Only the initial behaviors (i.e., the first sighting of an individual bird) were recorded to avoid problems related to non-independent data (Mansor and Ramli 2017;Mansor et al 2018a). Subsequent observations of foraging in the same bird were assumed to be correlated and were thus ignored (MacNally 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Our lack of detailed ecological knowledge of most species makes even hypothesizing likely networks of competitors difficult (Jankowski et al, 2012), beyond the relatively coarse metric of foraging guild or at the limited scale of genus. Diffuse competition may often result in niche differentiation based on foraging manoeuvres and strata rather than area occupancy, even among morphologically similar species with similar diets, as has been found for babblers (Timaliidae) in Malaysia (Mansor & Ramli, 2017;Styring, Ragai, Zakaria, & Sheldon, 2016). Competition may also be difficult to detect because elevational range overlap of strongly competing species may be effectively eliminated.…”
Section: Causes Of Occupancy Declines At Range Edgesmentioning
confidence: 99%